UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS 5 SD DENGAN MENGGUNAKAN CHIP BILANGAN - Hidayat Hidayat; Sukmawarti Sukmawarti; Nurul Fadilah (JS (JURNAL SEKOLAH), 2022)
Abstract: Student learning manifestations are seen as good or bad through the learning process carried out, both offline and online. Good learning is realized through effective and efficient learning activities. Good learning activities will have a direct effect on student learning success because the learning process cannot be separated from students' understanding of the learning material. The closeness of learning activities and learning outcomes is also expressed by Sudjana (2009:22) who explains that learning outcomes are abilities possessed by students after they receive their learning experiences. Based on the results of interviews and observations with the fifth grade elementary school teacher at the research location, the activeness of students during the learning process is also still very low so that only 37% of students can fulfill the KKM. To overcome this problem, the researcher invites students to determine the results of the operation of positive or negative numbers through a plate or chip. To improve student activity and learning outcomes, the authors carry out classroom action research (CAR) using number chip media. From the results of the study, it was found that the research was carried out through two cycles, so that it was found that student learning outcomes increased from an average of 62.25 in the first cycle to 79.75 at the end of the second cycle. Learning integer operations using the Number Chip media can increase the activity and learning outcomes of fifth grade elementary school students. Media Chip Numbers can increase the percentage of student learning success, namely from the percentage of completeness 60% in the first cycle to 100% in the second cycle. Student participation in carrying out student learning activities can be increased by using the Number Chip media.Keywords: learning activities, learning outcomes, chip numbers, integer operationsAbstrak: Manifestasi belajar siswa dilihat baik atau kurang baik melalui proses pembelajaran yang dilaksanakan, baik luring ataupun daring. Baiknya pembelajaran diwujudkan melalui aktivitas belajar yang efektif serta efisien. Aktivitas belajar yang baik akan memberikan efek langsung terhadap keberhasilan belajar siswa karena proses pembelajaran tidak lepas dengan pemahaman siswa terhadap materi pembelajaran. Eratnya aktivitas belajar dan hasil belajar juga diungkapkan oleh Sudjana (2009:22) yang menjelaskan bahwa hasil belajar adalah kemampuan-kemampuan yang dimiliki siswa setelah ia menerima pengalaman belajarnya. Berdasarkan hasil wawancara dan pengamatan dengan guru kelas V SD lokasi penelitian, keaktifan peserta didik selama proses pembelajaran juga masih sangat rendah sehingga hanya 37% siswa yang dapat memenuhi KKM. Untuk mengatasi permasalahan tersebut, peneliti mengajak siswa menentukan hasil dari operasi bilangan positif atau negatif melalui sebuah lempengan atau chip. Untuk meningkatkan aktivitas dan hasil belajar siswa, penulis melaksanakan penelitian tindakan kelas (PTK) dengan menggunakan media chip bilangan. Dari hasil penelitian diperoleh Penelitian dilakukan melalui dua siklus, sehingga diperoleh bahwa hasil belajar siswa meningkat dari rata-rata 62,25 pada siklus I menjadi 79,75 pada akhir siklus II. Pembelajaran operasi bilangan bulat dapat menggunakan media Chip Bilangan dapat meningkatkan aktivitas dan hasil belajar siswa kelas V SD. Media Chip Bilangan dapat meningkatkan persentasi keberhasilan belajar siswa yaitu dari persentasi ketuntasan 60% pada siklus I menajadi 100% pada siklus II. Partisipasi siswa dalam melaksanakan aktivitas belajar siswa dapat ditingkatkan dengan menggunakan media Chip Bilangan.Kata Kunci : Aktivitas belajar, Hasil Belajar, Chip Bilangan, Operasi Bilangan Bulat